Republic of Palau : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2006)
This 2005 Article IV Consultation highlights that Palau's economic growth has picked up in recent years while inflation has been low. After several years of slow growth, real GDP grew by 5 percent in FY2004 and FY2005, driven by a steady increase in visitor arrivals with the start of new airline routes and hotels. Economic prospects in the near term remain upbeat but are uncertain in the longer term. Tourism will continue to be a main source of near-term growth while ongoing externally financed large infrastructure projects will support construction and other services.